Pearson Correlation Study: Unveiling the Relationship between Demographic, Economic, and Health Factors in East Java - Susilowati, Dados; Adianita, Happy; Trifandha, Siskha (Gorontalo Development Review, 2025)
This study aims to elucidate the interactions among population size, urbanization, health, and average minimum wage in East Java Province, Indonesia. The research utilizes secondary data in the form of cross-sectional data sourced from the website of the Central Statistics Agency (BPS). The data analysis employed is correlation analysis to determine the relationships between the variables. The findings of the study indicate that 1) Population size and urbanization exhibit a strong positive correlation (r = 0.576) and are significant (p 0.05). Population size and health show a strong positive correlation (r = 0.726) and are significant (p 0.05). Population size and average minimum wage demonstrate a weak positive correlation (r = 0.285) and are significant (p 0.05). 2) Urbanization and health have a positive correlation (r = 0.417) and are significant (p 0.05). Urbanization and average minimum wage show nearly no correlation (r = -0.017) and are not significant (p 0.05). 3) Health and average minimum wage exhibit a positive correlation (r = 0.366) and are significant (p 0.05).